2020
DOI: 10.1136/bmjopen-2019-034849
|View full text |Cite
|
Sign up to set email alerts
|

Work-related psychosocial risk factors for stress-related mental disorders: an updated systematic review and meta-analysis

Abstract: ObjectiveThe objective was to conduct an update of a previously published review and meta-analysis on the association between work-related psychosocial risk factors and stress-related mental disorders (SRD).DesignSystematic review and meta-analysis.Data sourcesMedline, Embase and PsycINFO were searched for articles published between 2008 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
89
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 37 publications
10
89
0
8
Order By: Relevance
“…The work situation is a well-known stressor (17,19,20), which is also con rmed in our study. Different aspects of the work situation have been identi ed as predictors of stress , e.g.…”
Section: Predictorssupporting
confidence: 85%
See 3 more Smart Citations
“…The work situation is a well-known stressor (17,19,20), which is also con rmed in our study. Different aspects of the work situation have been identi ed as predictors of stress , e.g.…”
Section: Predictorssupporting
confidence: 85%
“…Our results are in accordance with the Stress Process Model, which nds that stressors combine to produce strain (24), and with previous studies reporting that combinations of stressors from both work and non-work domains contribute to mental health (18,23) and perceived stress in particular (3,31,32,66,67). However, our results are contrary to the vast majority of studies on stress that have focused on different aspects of the work situation and have concluded that the work situation causes stress and that related negative health effects are explained solely by the work situation (5,12,17,20,61,68,69). Our results are supported by a review reporting lack of knowledge about the relationship between work and non-work domains and their contribution to mental health (18).…”
Section: Main Ndings and Strati Ed Analysessupporting
confidence: 48%
See 2 more Smart Citations
“…Steigenden psychischen Störungen und daraus entstehende Fehlzeiten [23] aufgrund arbeitsbedingter, negativ ausgeprägter psychischer Belastungen [25] kommt daher eine zunehmend hohe Bedeutung zu. Der Zusammenhang zwischen der Ausprägung psychischer Belastung und entsprechenden Beanspruchungen und Beanspruchungsfolgen auf Seiten von Beschäftigten ist empirisch bestätigt [3,32] und fester Bestandteil internationaler Normen.…”
Section: Hintergrundunclassified